Estratégias didáticas para estudo da dinâmica rotacional - Busatto, Cassiano Zolet (2019)
The present study seeks didactic-methodological alternatives for an implementation of Rotational Dynamics topics in high school. The concern with the subject has origin of personal experiences of the researcher and also of data obtained from articles and dissertations that indicated the absence of this thematic in the basic education. According to this perception, and from the understanding that the lack of this subject implies a limited view of Newton's three Laws, the question that guides the investigation was formulated: How does problem-based teaching, supported by different teaching tools, contribute to the study of Rotational Dynamics? In order to respond to this questioning, we sought subsidies in constructivist conceptions of education, especially those based on the ideas of Laburu and Carvalho (2001), which suggest a teaching full of different didactic tools. From these choices, it was defined a general objective of the study, the evaluation of a didactic proposal to approach topics of Rotational Dynamics in high school. Aiming to develop the study, a proposal was elaborated containing different didactic tools, such as problematizations, digital resources and experimental activities. The research is defined as a qualitative and participatory approach, having as resources for the production of the data the teacher / researcher records, through logbook and pre and post -test questionnaires. The materials were analyzed using the Content Analysis method, proposed by Bardin (2004). The discussed results allowed us to infer that the use of diversified tools contributes to the dialogue between the members of the process, the visualization of abstract phenomena, the approximation with uncommon events and a broader view of the rotational movements. The educational product accompanying the study refers to a set of didactic tools that are available in the form of teacher support material, on the program site and the EduCapes portal <http://educapes.capes.gov.br/handle/capes/432305>